Boron Phosphorus Nitride at Extremes: PN6 Octahedra in the High‐Pressure Polymorph β‐BP3N6. Issue 27 (24th May 2019) - Vogel, Sebastian; Bykov, Maxim; Bykova, Elena; Wendl, Sebastian; Kloß, Simon D.; Pakhomova, Anna; Chariton, Stella; Koemets, Egor; Dubrovinskaia, Natalia; Dubrovinsky, Leonid; Schnick, Wolfgang
Abstract: The high‐pressure behavior of non‐metal nitrides is of special interest for inorganic and theoretical chemistry as well as materials science, as these compounds feature intriguing elastic properties. The double nitride α‐BP3 N6 was investigated by in situ single‐crystal X‐ray diffraction (XRD) upon cold compression to a maximum pressure of about 42 GPa, and its isothermal bulk modulus at ambient conditions was determined to be 146(6) GPa. At maximum pressure the sample was laser‐heated, which resulted in the formation of an unprecedented high‐pressure polymorph, β‐BP3 N6 . Its structure was elucidated by single‐crystal XRD, and can be described as a decoration of a distorted hexagonal close packing of N with B in tetrahedral and P in octahedral voids. Hence, β‐BP3 N6 is the first nitride to contain PN6 octahedra, representing the much sought‐after proof of principle for sixfold N‐coordinated P that has been predicted for numerous high‐pressure phases of nitrides. Abstract : Extreme conditions : α‐BP3 N6 was investigated in situ upon cold compression to a maximum pressure of 42 GPa, at which laser heating induced a phase transition into its high‐pressure polymorph β‐BP3 N6 . β‐BP3 N6 is the first nitride to contain PN6 octahedra, representing a much sought‐after structural motif in fundamental research on non‐metal nitrides.